Virtual screening of lead compounds for the treatment of Alzheimer's disease based on multi-target strategy. Issue 17 (22nd November 2022) - Li, Ruo-yu; Xie, Jia-li; Meng, Dan; Deng, Ping
ABSTRACT: Alzheimer's disease (AD) is a neurological illness that develops over time. Although the disease's origin and pathophysiology remain unclear, acetylcholinesterase (AChE) has been identified as a potential target. Other targets including glycogen synthase kinase 3 β (GSK-3 β ), β -secretase (BACE-1), and others, are also being investigated as possible therapeutic targets. In this work, compounds from the DrugBank and ZINC subset drug-like databases were screened in silico using ligand-based pharmacophore filtering and molecular docking. Two multi-target compounds, ZINC-27 and ZINC-1-4, were discovered utilising a combination of compound profiling, ADMET prediction, and structural modification, which can inhibit AChE, GSK-3 β, and BACE-1. Finally, the trustworthiness of the virtual screening findings was confirmed using molecular dynamics simulation, MM-PBSA binding free energy calculation, and principal component analysis. In conclusion, the multi-approach study revealed that ZINC-27 and ZINC-1-4 might be prospective multi-target anti-AD medicines that work concurrently on AChE, GSK-3 β, and BACE-1, which merit further investigation.